Profitabilitas Bank Syariah Ditinjau dari Pembiayaan dengan Prinsip Bagi Hasil dan Kategori Usaha - Purwanto Purwanto (Cakrawala: Jurnal Studi Islam, 2019)
As a business institution, the objectives of Islamic banking is profitability. The profit can be achieved if Islamic banking distributes financing both with the principle of buying and selling, profit sharing or services. The focus of the study was on financing with the principle of profit sharing (Mudharabah and Musyarakah). Profit sharing has been studied as a variable that can increase profitability, but there are no definite conclusions. Thus it is necessary to study whether the actual financing of profit sharing affects the level of profitability directly or through certain business categories. The type of research is causality research with a quantitative approach. The population is Sharia Commercial Banks and Sharia Business Units in the period of January 2016 to December 2018. The data analysis uses Partial Least Square (PLS). The results shows that financing with profit sharing principles is proven to directly have an influence on profitability but in a negative coefficient. This study also shows that the higher the profit sharing financing, the lower the level of profitability. However, when the revenue sharing is channeled through SMEs and non-SMEs, the results become positive and significant to profitability